2016
DOI: 10.1093/cid/ciw050
|View full text |Cite
|
Sign up to set email alerts
|

Whole-Genome Sequencing Reveals the Origin and Rapid Evolution of an Emerging Outbreak Strain ofStreptococcus pneumoniae12F

Abstract: Background. Streptococcus pneumoniae is a major cause of community-acquired pneumonia and septicemia in adults. The global drug-susceptible capsular serotype 12F, clonal complex 218 caused several outbreaks in the United States between 1989 and 2008, as well as a recent large outbreak in Manitoba, Canada, that resulted in 36 cases of septicemia and 3 deaths. The evolutionary origin of the Canadian outbreak strain and its relationship to the historical US outbreak strains are not known.Methods. Whole-genome dee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
22
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 22 publications
1
22
0
Order By: Relevance
“…One of the most prevalent S. pneumoniae serotypes, 12F (14%), has undergone whole-genome sequencing, revealing secondary adaptation to a new virulent and drugresistant form (Deng et al, 2016). This form was first identified in an epidemic in Manitoba, Canada (geographically very close to Northwestern Ontario), and has since spread to multiple sites across Canada and the USA (Deng et al, 2016). In the paediatric population of this study, all IPD cases were caused by non-PCV serotypes.…”
Section: Streptococcus Pneumoniaementioning
confidence: 73%
See 1 more Smart Citation
“…One of the most prevalent S. pneumoniae serotypes, 12F (14%), has undergone whole-genome sequencing, revealing secondary adaptation to a new virulent and drugresistant form (Deng et al, 2016). This form was first identified in an epidemic in Manitoba, Canada (geographically very close to Northwestern Ontario), and has since spread to multiple sites across Canada and the USA (Deng et al, 2016). In the paediatric population of this study, all IPD cases were caused by non-PCV serotypes.…”
Section: Streptococcus Pneumoniaementioning
confidence: 73%
“…Although the PPV-23 vaccine protects against the most virulent and prevalent pneumococcal serotypes (1, 2, 3, 4, 5, 6B, 7F, 8, 9N, 9V, 10A, 11A, 12F, 14, 15B, 17F, 18C, 19A, 19F, 20, 22F, 23F, and 33F) and is effective in preventing adult IPD, it is less effective against non-invasive infections and is ineffective in young children (Kellner and Tyrrell, 2005).Of note, the PPV-23 vaccine contains the serotypes of 70.3% of all identified S. pneumoniae serotypes for SLMHC cases (67.7% of cases in people >5 years; 62.5% of cases in people >65 years). One of the most prevalent S. pneumoniae serotypes, 12F (14%), has undergone whole-genome sequencing, revealing secondary adaptation to a new virulent and drugresistant form (Deng et al, 2016). This form was first identified in an epidemic in Manitoba, Canada (geographically very close to Northwestern Ontario), and has since spread to multiple sites across Canada and the USA (Deng et al, 2016).…”
Section: Streptococcus Pneumoniaementioning
confidence: 99%
“…Increases in serotype 12F resulting in disease replacement were reported in England and Wales, 6 France, 9,40 and Germany, 39 although the genotypes of those isolates were not reported. Globally, serotype 12F isolates mainly belong to clonal complex (CC) 989 (GPSC26), 41,42 but also to ST218 (GPSC32) in North America 43,44 and CC3524 (GPSC55), a regional lineage, in Israel. Increase in serotype 8 was also observed among children less than 5 years of age in England and Wales in 2016-17.…”
Section: Discussionmentioning
confidence: 99%
“…16 However, the Winnipeg outbreak was caused by a rapidly evolving novel 12F clone, ST218, that acquired both macrolide and fluoroquinolone resistance via recombination with a 5.3 kb mega gene cassette harboring msrD and mefE as well as several mutations. 17 The Manitoba clone appears to have spread to neighboring Canadian and US jurisdictions replacing drug-sensitive strains. 17 Our study confirmed that the burden of IPD in Manitoba remained high among groups previously identified at higher risk including the poor and those with chronic diseases.…”
Section: Discussionmentioning
confidence: 99%
“…17 The Manitoba clone appears to have spread to neighboring Canadian and US jurisdictions replacing drug-sensitive strains. 17 Our study confirmed that the burden of IPD in Manitoba remained high among groups previously identified at higher risk including the poor and those with chronic diseases. Manitoba's overall rates were in line with Canadian rates, whereas the rates reported in northern Manitoba and inner city Winnipeg, both communities that are socio-economically disadvantaged and pre-dominantly of indigenous ethnicity, were significantly higher.…”
Section: Discussionmentioning
confidence: 99%